Effects of Anodization-Assisted Electrodeposition Conditions on the Fabrication of CuO-Cu2O Coatings on Nanoporous Stainless Steel - Hefeng Wang; Jiaojiao Zhang; Xiaomin Jin (Advances in Materials Science and Engineering)
Surface functionalization can be utilized as a useful tool to improve the antibacterial performances of medical devices. Furthermore, some antibacterial agents are coated or impregnated on the surface of 316LSS to prevent contamination of bacteria. Here, CuO-Cu2O coatings were prepared on 316L nanoporous stainless steel (NPSS) by anodization-assisted electrodeposition for applications in antibacterial materials. The present study investigated influences of HClO4 concentration, reaction temperature, and load voltage on the morphology, structure, and composition of the coatings. SEM images showed that appropriate nanopores with an average size of about 93 nm were formed on the stainless steel surface and then were successfully filled with CuO-Cu2O. The nanopore size increased with increasing application of electrolyte concentration. Both the diameter and depth of the nanopores increased with increasing voltage. The EDX result indicated that Cu and O were embedded in as-prepared CuO-Cu2O/NPSS. XRD analysis showed that the CuO-Cu2O/NPSS surface comprised CuO and Cu2O.